The Nutritional Status of Pregnant Women Related to Low Birth Weight (LBW) - Dwi Listiarini, Utary; Maryanti, Endang; Sofiah, Nur Sahira (Jurnal Kesehatan Mahardika, 2022)
Babies born with low birth weight (LBW) is an indirect cause of neonatal death. It contributes 60% to 80% of all neonatal deaths and based on an initial survey. The incidence of LBW is 30 babies out of 90 births due to the nutritional status of the mother during pregnancy. The purpose of this study was to determine the relationship between nutritional status of pregnant women and LBW. This study used a retrospective cohort study. The population and sample were all mothers who gave birth with LBW in June 2020 - June 2021 was done using secondary data, analysis used chiSquare. The results showed that the majority of mothers who were malnourished (93.3%) had low baby weight (83.3%). Based on the results of the chi-square test between nutritional status based on upper arm circumference and low birth weight obtained p-value = 1.00 and between nutritional status based on BMI and low birth weight obtained p-value .029. The conclusion in this study shows that there is a significant relationship between nutritional status based on upper arm circumferenceand and BMI with LBW, It is expected that midwives at the Clinic to increase counseling about nutrition during pregnancy to prevent birth LBW.